The Comparison of Persian Shallot and Garlic Hydroalcoholic Extracts on Albumin Glycation - Seyed Mostafa Hosseini; Hassan Ghasemi; Younes Moradi; Akram Ranjbar (Novelty in Clinical Medicine, 2022)
Background: Hyperglycemia in diabetes leads to body protein glycation, consequently altering their structure and function and causing later complications. So, inhibition of protein glycation reaction or breaking this linkage for reducing or improving diabetes complications seems so necessary.Objectives: In the current study the effect of Persian Shallot and garlic hydroalcholic extracts on the amount of in vitro albumin glycation was compared.Methods: In this experimental study, the effect of 0.1, 0.2, and 1 gr/dl concentration of Persian shallot and garlic extracts, on inhibition of albumin glycation reaction was compared. The amount of glycation was assayed by TBA (Thiobarbituric Acid).Results: The Persian shallot and garlic extracts in all concentrations inhibit the albumin glycation reaction and the 1 g/dl concentration was the most effective and the differences were significant (P<0.05). The rate of linkage breaking has a direct relation to concentration and the time period of treatment. The observed inhibitory effects showed a significant difference between Persian shallot and garlic extract only at a concentration of 1 g/dl in 48 hours of treatment, which showed that Persian shallot had a greater effect. Conclusion: The current findings demonstrate that Persian shallot and garlic similarly prevent albumin glycation and also break the linkage between albumin and glucose.